Implementation Of Learning Index Card Match To Improve The Outcome Of Science Class IV MI Darul Qur'an Al Hasan Nw Peresak - Zohri Ratna (Tinta Emas Publisher, 2023)
This study aims to see the impact of implementing Index Card Match learning in improving science learning outcomes for class IV MI Darul Qur'an Al Hasan NW Peresak. This type of research is classroom action research with a recycling cycle consisting of four stages, namely (a) planning, (b) implementation, (c) observation and (d) reflection. Data were collected through observation sheets, documentation studies, and tests in each cycle. The results showed that the average student learning outcomes had increased. The percentage of completeness also increased. In the pre-study the percentage of completeness was 37.5%. cycle I was 66.66% and cycle II was 87.05%. Thus the Index Card Match learning strategy can improve student learning outcomes in science subjects in class IV MI Darul Qur'an Al Hasan NW Peresak